Water-resistant polyvinyl alcohol optical adhesive as well as preparation method and application thereof

By using a water-resistant polyvinyl alcohol optical follower with a specific ratio in the polarizing plate, combined with the stacking assembly and chemical bond crosslinking of lithium magnesium powder, the water resistance problem of the polarizing plate under high temperature and high humidity conditions is solved, and the support is not changed. The effect of significantly improving water resistance in the case of materials and equipment.

CN119307196APending Publication Date: 2025-01-14FOSHAN WEIDA OPTOELECTRONIC MATERIALS CO LTD

Patent Information

Application Number
CN202411593490.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Existing polarizing plates are susceptible to water vapor erosion under high temperature and high humidity conditions, resulting in a decrease in bonding capacity. The existing improved methods require replacement of supporting materials or adding equipment, which is costly.

Method used

A water-resistant polyvinyl alcohol optical adhesion agent is adopted, containing deionized water, polyvinyl alcohol, lithiumite powder, glutaraldehyde and metal salts. Through specific ratios and processes, an organic/inorganic hybrid composite adhesion agent is formed. Enhance its water resistance.

Benefits of technology

Without changing the support materials and equipment of the polarizing plate, the high temperature and high humidity resistance of the polarizing plate is significantly improved, through the lamination assembly and hydrogen bonding of lithium magnesium powder, as well as glutaraldehyde, polyethyleneimine and polyvinyl alcohol Chemical bond crosslinking forms complex networks and enhances its water resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307196A_ABST
    Figure CN119307196A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of optical adhesion agents, and discloses a water-resistant polyvinyl alcohol optical adhesion agent and a preparation method and application thereof, and the water-resistant polyvinyl alcohol optical adhesion agent comprises the following components in parts by weight: 88-95 parts of deionized water, 4-7 parts of polyvinyl alcohol, 0.1-2 parts of lithium magnesium stone powder, 0.1-2 parts of glutaraldehyde, 0.1-0.5 part of metal salt and 0.1-2 parts of polyethyleneimine. The water-resistant polyvinyl alcohol optical adhesive has the advantages that the water resistance of a polarizing plate can be effectively enhanced by the prepared water-resistant polyvinyl alcohol optical adhesive due to the laminated assembly trend and the strong hydrogen-bond interaction of the lithium magnesium stone powder and binary, ternary and multi-element chemical bonds formed by glutaraldehyde, polyethyleneimine and metal salt with acetoacetyl functional groups in the polyvinyl alcohol respectively.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of optical adhesives, and particularly relates to a water-resistant polyvinyl alcohol optical adhesive and a preparation method and application thereof. Background Art

[0002] Display screens have a wide range of uses due to their dynamic display capabilities and intelligent interactive features. They are increasingly used in daily work, entertainment, advertising, education and other fields. Therefore, the reliability of display screens is becoming increasingly important. Polarizers are an indispensable component in display screens, and their weather resistance directly affects the display effect.

[0003] Generally speaking, polarizing plates are made of polyvinyl alcohol film dyed with iodine or dye and stretched and supporting material triacetate cellulose film bonded by polyvinyl alcohol optical adhesive. Under high temperature and high humidity conditions, the polyvinyl alcohol optical adhesive in the polarizing plate is easily corroded by water vapor and loses its bonding ability, resulting in a decrease in the polarization effect.

[0004] At present, the main methods to improve the high temperature and high humidity resistance of polarizing plates include selecting low moisture permeability materials such as cycloolefin polymer (COP) and polymethyl methacrylate (PMMA) to replace triacetyl cellulose film, using photocuring adhesives to bond triacetyl cellulose film and polyvinyl alcohol film, or a combination of the two. For example, patent TWI386472B uses acrylic film to replace triacetyl cellulose film to achieve significant improvement in water resistance; patent US10858553B2 reveals the difference in water resistance of different photocuring adhesive formulations. Patent US11008485B2 discloses a case in which the water resistance of a product is greatly improved when COP film materials are used in combination with appropriate photocuring adhesive formulations. However, these methods require the replacement of the supporting materials of the polarizer or the installation of additional UV curing equipment on the production line, which requires a large investment cost.

[0005] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a water-resistant polyvinyl alcohol optical adhesive and a preparation method and application thereof, aiming to improve the high temperature and high humidity resistance of the polarizing plate without changing the supporting material of the polarizing plate or adjusting the production line equipment.

[0007] The technical solution of the present invention is as follows:

[0008] A water-resistant polyvinyl alcohol optical adhesive comprises, by weight: 88-95 parts of deionized water, 4-7 parts of polyvinyl alcohol, 0.1-2 parts of leonite powder, 0.1-2 parts of glutaraldehyde, 0.1-0.5 parts of metal salt, and 0.1-2 parts of polyethyleneimine.

[0009] The water-resistant polyvinyl alcohol optical adhesive, wherein the average polymerization degree of the polyvinyl alcohol is 1000-2500.

[0010] The water-resistant polyvinyl alcohol optical adhesive has a saponification degree of 90-99%.

[0011] The water-resistant polyvinyl alcohol optical adhesive, wherein the average polymerization degree of the polyethyleneimine is 1000-2500.

[0012] The water-resistant polyvinyl alcohol optical adhesive, wherein the length and width of the hectorite powder are both between 0.3-1 μm, and the thickness of the powder is between 0.01-0.04 μm.

[0013] The water-resistant polyvinyl alcohol optical adhesive, wherein the metal salt is one or more of magnesium chloride, magnesium sulfate, aluminum chloride, aluminum sulfate, zirconium chloride and zirconium sulfate.

[0014] A method for preparing the water-resistant polyvinyl alcohol optical adhesive according to the present invention comprises the following steps:

[0015] Mix polyvinyl alcohol and deionized water according to weight ratio, heat to 90-95°C, add levofloxacin powder after stirring, and continue stirring to obtain a semi-finished adhesive;

[0016] Add metal salt to the semi-finished adhesive in parts by weight, then cool the semi-finished adhesive to 25-30° C., add polyethyleneimine and glutaraldehyde in sequence, and continue stirring to obtain the water-resistant polyvinyl alcohol optical adhesive.

[0017] An application of the water-resistant polyvinyl alcohol optical adhesive according to the present invention, wherein the water-resistant polyvinyl alcohol optical adhesive is used to prepare a polarizing plate.

[0018] The application, wherein the preparation of the polarizing plate comprises the steps of:

[0019] The water-resistant polyvinyl alcohol optical adhesive is applied on the upper and lower surfaces of the polyvinyl alcohol film dyed with iodine or dye and stretched by roller coating;

[0020] The upper and lower surfaces of the polyvinyl alcohol film are respectively laminated to the triacetyl cellulose film by roller lamination, and after lamination, segmented drying is performed to obtain the polarizing plate.

[0021] In the application, the temperature of the segmented drying is 40-100° C., and the thickness of the water-resistant polyvinyl alcohol optical adhesive after drying is 2-5 μm.

[0022] Beneficial effect: The technical scheme of the present invention can be used to prepare an organic / inorganic hybrid polyvinyl alcohol optical adhesive. The lithium magnesium stone powder in the adhesive has a flaky nano morphology. The flaky edge of the nano material carries a positive charge due to the protonation of magnesium ions, and the positive charge density of the flaky front and back sides decreases due to the replacement of magnesium ions by lithium ions. The existence of the regional potential difference of the nano material makes the flaky nano material itself have a stacking assembly trend. At the same time, the flaky edge of the nano material can form a pair with the lone pair of electrons of the oxygen atom on the hydroxyl group of polyvinyl alcohol to form a hydrogen bond, and the flaky front and back sides can also form a hydrogen bond with the hydroxyl hydrogen atom of polyvinyl alcohol. Polyvinyl alcohol and lithium magnesium stone powder can be well blended with each other without phase separation to form an organic / inorganic hybrid composite adhesive, which enhances water resistance. Glutaraldehyde, polyethyleneimine, and metal salts can form binary, ternary, and multi-component chemical bonds with the acetoacetyl functional group in polyvinyl alcohol, respectively, and the adhesive can form a complex cross-linked network to enhance water resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a schematic diagram of the structure of the polarizing plate prepared in Example 1 of the present invention.

[0024] Figure 2 The following are pictures showing the effects of the polarizing plates prepared in Example 1 and Comparative Example 1 being tested in a cooking box (condition: 100° C.*100% RH) for 30 and 60 minutes. DETAILED DESCRIPTION

[0025] The present invention will be further described below in conjunction with specific examples. These embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually based on normal conditions. Unless otherwise stated, all percentages, ratios, ratios, or percentages are calculated by mass.

[0026] Unless otherwise specified, all professional and scientific terms used herein have the same meanings as those known to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein can be used in the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only.

[0027] Comparative Example 1

[0028] A water-resistant polyvinyl alcohol optical adhesive is prepared by mixing the following components in parts by weight: 95.5 parts of deionized water, 4 parts of polyvinyl alcohol powder (average degree of polymerization 2500, degree of saponification 98%), 0.3 parts of glutaraldehyde and 0.2 parts of polyethyleneimine.

[0029] Step 1: Add deionized water to the container, keep it warm at 30°C and stir evenly, then add polyvinyl alcohol powder to the beaker in small amounts and multiple times, stir and disperse at high speed for 1 hour, then heat to 95°C and stir for 2 hours until the polyvinyl alcohol is completely dissolved to obtain a semi-finished adhesive.

[0030] Step 2: Cool the semi-finished adhesive to 25-30° C., add glutaraldehyde and polyethyleneimine to obtain a polyvinyl alcohol optical adhesive.

[0031] Step 3: Use roller coating to apply polyvinyl alcohol optical adhesive on the upper and lower surfaces of the polyvinyl alcohol film that has been dyed with iodine or dye and stretched, and then laminate the upper and lower surfaces of the film with triacetate cellulose film by roller lamination to form a polarizing plate. After lamination, segmented drying is adopted, with a total of 6 stages of drying, and the drying temperatures of each stage are 55, 60, 65, 70, 75, 80, and 80°C.

[0032] Example 1

[0033] A water-resistant polyvinyl alcohol optical adhesive is prepared by mixing the following components in parts by weight: 94 parts of deionized water, 4 parts of polyvinyl alcohol powder (average polymerization degree 1000, saponification degree 92%), 1 part of leonite powder, 0.3 parts of glutaraldehyde, 0.5 parts of aluminum chloride and 0.2 parts of polyethyleneimine.

[0034] The preparation of the polarizing plate includes the following steps:

[0035] Step 1: Add deionized water to the container, keep it warm at 30°C and stir evenly, then add polyvinyl alcohol powder to the beaker in small amounts and multiple times, stir and disperse at high speed for 1 hour, then heat to 95°C, stir for 2 hours, until the polyvinyl alcohol is completely dissolved; then add lithium magnesium powder, continue stirring for 2 hours, during which the mass of deionized water that is volatilized and reduced is supplemented to ensure the solid content of the stock solution, and obtain a semi-finished adhesive.

[0036] Step 2: adding aluminum chloride to the semi-finished adhesive, stirring at high speed for 10 minutes, cooling the semi-finished adhesive to 25-30° C., adding glutaraldehyde and polyethyleneimine, and obtaining a water-resistant polyvinyl alcohol optical adhesive;

[0037] Step 3: Use roller coating to apply water-resistant polyvinyl alcohol optical adhesive on the upper and lower surfaces of the polyvinyl alcohol film dyed with iodine or dye and stretched, and then laminate the upper and lower surfaces of the polyvinyl alcohol film with triacetyl cellulose film by roller lamination to obtain Figure 1 The polarizing plate shown in the figure; after lamination, segmented drying is adopted, with a total of 6 stages of drying, and the drying temperatures of each stage are 55, 60, 65, 70, 75, 80, and 80°C.

[0038] Example 2

[0039] A water-resistant polyvinyl alcohol optical adhesive is prepared by mixing the following components in parts by weight: 94 parts of deionized water, 4 parts of polyvinyl alcohol powder (average polymerization degree 1000, saponification degree 99%), 1 part of leonite powder, 0.2 parts of glutaraldehyde, 0.25 parts of aluminum sulfate and 0.55 parts of polyethyleneimine.

[0040] The preparation of the polarizing plate includes the following steps:

[0041] Step 1: Add deionized water to the container, keep it warm at 30°C and stir evenly, then add polyvinyl alcohol powder to the beaker in small amounts and multiple times, stir and disperse at high speed for 1 hour, then heat to 95°C, stir for 2 hours, until the polyvinyl alcohol is completely dissolved; then add lithium magnesium powder, continue stirring for 2 hours, during which the mass of deionized water that is volatilized and reduced is supplemented to ensure the solid content of the stock solution, and obtain a semi-finished adhesive.

[0042] Step 2: adding aluminum sulfate to the semi-finished adhesive, stirring at high speed for 15 minutes, cooling the semi-finished adhesive to 25-30° C., adding glutaraldehyde and polyethyleneimine, and obtaining a water-resistant polyvinyl alcohol optical adhesive.

[0043] Step 3: Use roller coating to apply water-resistant polyvinyl alcohol optical adhesive on the upper and lower surfaces of the polyvinyl alcohol film that has been dyed with iodine or dye and stretched, and then laminate the upper and lower surfaces of the polyvinyl alcohol film with triacetyl cellulose film by roller lamination to form a polarizing plate. After lamination, segmented drying is adopted, with a total of 6 stages of drying, and the drying temperatures of each stage are 55, 60, 65, 70, 75, 80, and 80°C.

[0044] Example 3

[0045] A water-resistant polyvinyl alcohol optical adhesive is prepared by mixing the following components in parts by weight: 94 parts of deionized water, 4 parts of polyvinyl alcohol powder (average polymerization degree 2500, saponification degree 98%), 1 part of leonite powder, 0.1 part of glutaraldehyde, 0.1 part of magnesium sulfate and 0.8 part of polyethyleneimine.

[0046] The preparation of the polarizing plate includes the following steps:

[0047] Step 1: Add deionized water to the container, keep it warm at 30°C and stir evenly, then add polyvinyl alcohol powder to the beaker in small amounts and multiple times, stir and disperse at high speed for 1 hour, then heat to 95°C, stir for 2 hours, until the polyvinyl alcohol is completely dissolved; then add lithium magnesium powder, continue stirring for 2 hours, during which the mass of deionized water that is volatilized and reduced is supplemented to ensure the solid content of the stock solution, and obtain a semi-finished adhesive.

[0048] Step 2: Add magnesium sulfate to the semi-finished adhesive, stir at high speed for 15 minutes, cool the semi-finished adhesive to 25-30° C., add glutaraldehyde and polyethyleneimine to obtain a water-resistant polyvinyl alcohol optical adhesive.

[0049] Step 3: Use roller coating to apply water-resistant polyvinyl alcohol optical adhesive on the upper and lower surfaces of the polyvinyl alcohol film that has been dyed with iodine or dye and stretched, and then use roller lamination to laminate the upper and lower surfaces of the polyvinyl alcohol film with triacetyl cellulose film to form a polarizing plate. After lamination, use segmented drying for a total of 6 stages, and the drying temperatures of each stage are 60, 65, 70, 70, 75, 85, and 85°C.

[0050] Example 4

[0051] A water-resistant polyvinyl alcohol optical adhesive is prepared by mixing the following components in parts by weight: 94 parts of deionized water, 4 parts of polyvinyl alcohol powder (average polymerization degree 2500, saponification degree 98%), 1 part of leonite powder, 0.1 part of glutaraldehyde, 0.1 part of magnesium chloride and 0.8 part of polyethyleneimine.

[0052] The preparation of the polarizing plate includes the following steps:

[0053] Step 1: Add deionized water to the container, keep it warm at 30°C and stir evenly, then add polyvinyl alcohol powder to the beaker in small amounts and multiple times, stir and disperse at high speed for 1 hour, then heat to 95°C, stir for 2 hours, until the polyvinyl alcohol is completely dissolved; then add lithium magnesium powder, continue stirring for 2 hours, during which the mass of deionized water that is volatilized and reduced is supplemented to ensure the solid content of the stock solution, and obtain a semi-finished adhesive.

[0054] Step 2: Add magnesium chloride to the semi-finished adhesive, stir at high speed for 15 minutes, cool the semi-finished adhesive to 25-30° C., add glutaraldehyde and polyethyleneimine to obtain a water-resistant polyvinyl alcohol optical adhesive.

[0055] Step 3: Use roller coating to apply water-resistant polyvinyl alcohol optical adhesive on the upper and lower surfaces of the polyvinyl alcohol film that has been dyed with iodine or dye and stretched, and then use roller lamination to laminate the upper and lower surfaces of the polyvinyl alcohol film with triacetyl cellulose film to form a polarizing plate. After lamination, use segmented drying for a total of 6 stages, and the drying temperatures of each stage are 60, 65, 70, 70, 75, 85, and 85°C.

[0056] Example 5

[0057] A water-resistant polyvinyl alcohol optical adhesive is prepared by mixing the following components in parts by weight: 93.5 parts of deionized water, 3.5 parts of polyvinyl alcohol powder (average degree of polymerization 1000, degree of saponification 92%), 1.5 parts of leonite powder, 0.4 parts of glutaraldehyde, 0.5 parts of aluminum chloride and 0.6 parts of polyethyleneimine.

[0058] The preparation of the polarizing plate includes the following steps:

[0059] Step 1: Add deionized water to the container, keep it warm at 30°C and stir evenly, then add polyvinyl alcohol powder to the beaker in small amounts and multiple times, stir and disperse at high speed for 1 hour, then heat to 95°C, stir for 2 hours, until the polyvinyl alcohol is completely dissolved; then add lithium magnesium powder, continue stirring for 2 hours, during which the mass of deionized water that is volatilized and reduced is supplemented to ensure the solid content of the stock solution, and obtain a semi-finished adhesive.

[0060] Step 2: adding aluminum chloride to the semi-finished adhesive, stirring at high speed for 15 minutes, cooling the semi-finished adhesive to 25-30° C., adding glutaraldehyde and polyethyleneimine, and obtaining a water-resistant polyvinyl alcohol optical adhesive.

[0061] Step 3: Use roller coating to apply water-resistant polyvinyl alcohol optical adhesive on the upper and lower surfaces of the polyvinyl alcohol film that has been dyed with iodine or dye and stretched, and then use roller lamination to laminate the upper and lower surfaces of the polyvinyl alcohol film with triacetyl cellulose film to form a polarizing plate. After lamination, use segmented drying for a total of 6 stages, and the drying temperatures of each stage are 60, 60, 65, 70, 75, 85, and 85°C.

[0062] Example 6

[0063] A water-resistant polyvinyl alcohol optical adhesive is prepared by mixing the following components in parts by weight: 93.2 parts of deionized water, 3.5 parts of polyvinyl alcohol powder (average polymerization degree 1000, saponification degree 99%), 1.5 parts of leonite powder, 0.3 parts of glutaraldehyde, 0.25 parts of aluminum sulfate and 1.25 parts of polyethyleneimine.

[0064] The preparation of the polarizing plate includes the following steps:

[0065] Step 1: Add deionized water to the container, keep it warm at 30°C and stir evenly, then add polyvinyl alcohol powder to the beaker in small amounts and multiple times, stir and disperse at high speed for 1 hour, then heat to 95°C, stir for 2 hours, until the polyvinyl alcohol is completely dissolved; then add lithium magnesium powder, continue stirring for 2 hours, during which the mass of deionized water that is volatilized and reduced is supplemented to ensure the solid content of the stock solution, and obtain a semi-finished adhesive.

[0066] Step 2: adding aluminum sulfate to the semi-finished adhesive, stirring at high speed for 15 minutes, cooling the semi-finished adhesive to 25-30° C., adding glutaraldehyde and polyethyleneimine, and obtaining a water-resistant polyvinyl alcohol optical adhesive.

[0067] Step 3: Use roller coating to apply water-resistant polyvinyl alcohol optical adhesive on the upper and lower surfaces of the polyvinyl alcohol film that has been dyed with iodine or dye and stretched, and then use roller lamination to laminate the upper and lower surfaces of the polyvinyl alcohol film with triacetyl cellulose film to form a polarizing plate. After lamination, use segmented drying for a total of 6 stages, and the drying temperatures of each stage are 60, 60, 65, 70, 75, 85, and 85°C.

[0068] Example 7

[0069] A water-resistant polyvinyl alcohol optical adhesive is prepared by mixing the following components in parts by weight: 93.2 parts of deionized water, 3.5 parts of polyvinyl alcohol powder (average polymerization degree 2500, saponification degree 98%), 1.5 parts of leonite powder, 0.3 parts of glutaraldehyde, 0.25 parts of magnesium sulfate and 1.25 parts of polyethyleneimine.

[0070] The preparation of the polarizing plate includes the following steps:

[0071] Step 1: Add deionized water to the container, keep it warm at 30°C and stir evenly, then add polyvinyl alcohol powder to the beaker in small amounts and multiple times, stir and disperse at high speed for 1 hour, then heat to 95°C, stir for 2 hours, until the polyvinyl alcohol is completely dissolved; then add lithium magnesium powder, continue stirring for 2 hours, during which the mass of deionized water that is volatilized and reduced is supplemented to ensure the solid content of the stock solution, and obtain a semi-finished adhesive.

[0072] Step 2: Add magnesium sulfate to the semi-finished adhesive, stir at high speed for 15 minutes, cool the semi-finished adhesive to 25-30° C., add glutaraldehyde and polyethyleneimine to obtain a water-resistant polyvinyl alcohol optical adhesive.

[0073] Step 3: Use roller coating to apply water-resistant polyvinyl alcohol optical adhesive on the upper and lower surfaces of the polyvinyl alcohol film that has been dyed with iodine or dye and stretched, and then use roller lamination to laminate the upper and lower surfaces of the polyvinyl alcohol film with triacetyl cellulose film to form a polarizing plate. After lamination, use segmented drying for a total of 6 stages, and the drying temperatures of each stage are 60, 60, 65, 70, 75, 85, and 85°C.

[0074] Example 8

[0075] A water-resistant polyvinyl alcohol optical adhesive is prepared by mixing the following components in parts by weight: 93.2 parts of deionized water, 3.5 parts of polyvinyl alcohol powder (average polymerization degree 2500, saponification degree 98%), 1.5 parts of leonite powder, 0.3 parts of glutaraldehyde, 0.25 parts of magnesium chloride and 1.25 parts of polyethyleneimine.

[0076] The preparation of the polarizing plate includes the following steps:

[0077] Step 1: Add deionized water to the container, keep it warm at 30°C and stir evenly, then add polyvinyl alcohol powder to the beaker in small amounts and multiple times, stir and disperse at high speed for 1 hour, then heat to 95°C, stir for 2 hours, until the polyvinyl alcohol is completely dissolved; then add lithium magnesium powder, continue stirring for 2 hours, during which the mass of deionized water that is volatilized and reduced is supplemented to ensure the solid content of the stock solution, and obtain a semi-finished adhesive.

[0078] Step 2: Add magnesium chloride to the semi-finished adhesive, stir at high speed for 15 minutes, cool the semi-finished adhesive to 25-30° C., add glutaraldehyde and polyethyleneimine to obtain a water-resistant polyvinyl alcohol optical adhesive.

[0079] Step 3: Use roller coating to apply water-resistant polyvinyl alcohol optical adhesive on the upper and lower surfaces of the polyvinyl alcohol film that has been dyed with iodine or dye and stretched, and then use roller lamination to laminate the upper and lower surfaces of the polyvinyl alcohol film with triacetyl cellulose film to form a polarizing plate. After lamination, use segmented drying for a total of 6 stages, and the drying temperatures of each stage are 60, 60, 65, 70, 75, 85, and 85°C.

[0080] Example 9

[0081] A water-resistant polyvinyl alcohol optical adhesive is prepared by mixing the following components in parts by weight: 94.5 parts of deionized water, 3 parts of polyvinyl alcohol powder (average polymerization degree 1000, saponification degree 92%), 1 part of leonite powder, 0.4 parts of glutaraldehyde, 0.5 parts of zirconium chloride and 0.6 parts of polyethyleneimine.

[0082] The preparation of the polarizing plate includes the following steps:

[0083] Step 1: Add deionized water to the container, keep it warm at 30°C and stir evenly, then add polyvinyl alcohol powder to the beaker in small amounts and multiple times, stir and disperse at high speed for 1 hour, then heat to 95°C, stir for 2 hours, until the polyvinyl alcohol is completely dissolved; then add lithium magnesium powder, continue stirring for 2 hours, during which the mass of deionized water that is volatilized and reduced is supplemented to ensure the solid content of the stock solution, and obtain a semi-finished adhesive.

[0084] Step 2: Add zirconium chloride to the semi-finished adhesive, stir at high speed for 15 minutes, cool the semi-finished adhesive to 25-30° C., add glutaraldehyde and polyethyleneimine to obtain a water-resistant polyvinyl alcohol optical adhesive.

[0085] Step 3: Use roller coating to apply water-resistant polyvinyl alcohol optical adhesive on the upper and lower surfaces of the polyvinyl alcohol film that has been dyed with iodine or dye and stretched, and then use roller lamination to laminate the upper and lower surfaces of the polyvinyl alcohol film with triacetyl cellulose film to form a polarizing plate. After lamination, use segmented drying for a total of 6 stages, and the drying temperatures of each stage are 60, 60, 65, 70, 75, 85, and 85°C.

[0086] Example 10

[0087] A water-resistant polyvinyl alcohol optical adhesive is prepared by mixing the following components in parts by weight: 94.2 parts of deionized water, 3 parts of polyvinyl alcohol powder (average degree of polymerization 1000, degree of saponification 99%), 1 part of leonite powder, 0.3 parts of glutaraldehyde, 0.25 parts of zirconium chloride and 1.25 parts of polyethyleneimine.

[0088] The preparation of the polarizing plate includes the following steps:

[0089] Step 1: Add deionized water to the container, keep it warm at 30°C and stir evenly, then add polyvinyl alcohol powder to the beaker in small amounts and multiple times, stir and disperse at high speed for 1 hour, then heat to 95°C, stir for 2 hours, until the polyvinyl alcohol is completely dissolved; then add lithium magnesium powder, continue stirring for 2 hours, during which the mass of deionized water that is volatilized and reduced is supplemented to ensure the solid content of the stock solution, and obtain a semi-finished adhesive.

[0090] Step 2: Add zirconium chloride to the semi-finished adhesive, stir at high speed for 15 minutes, cool the semi-finished adhesive to 25-30° C., add glutaraldehyde and polyethyleneimine to obtain a water-resistant polyvinyl alcohol optical adhesive.

[0091] Step 3: Use roller coating to apply water-resistant polyvinyl alcohol optical adhesive on the upper and lower surfaces of the polyvinyl alcohol film that has been dyed with iodine or dye and stretched, and then use roller lamination to laminate the upper and lower surfaces of the polyvinyl alcohol film with triacetyl cellulose film to form a polarizing plate. After lamination, use segmented drying for a total of 6 stages, and the drying temperatures of each stage are 60, 60, 65, 70, 75, 85, and 85°C.

[0092] Embodiment 11

[0093] A water-resistant polyvinyl alcohol optical adhesive is prepared by mixing the following components in parts by weight: 94.2 parts of deionized water, 3 parts of polyvinyl alcohol powder (average polymerization degree 2500, saponification degree 98%), 1 part of leonite powder, 0.2 parts of glutaraldehyde, 0.25 parts of zirconium chloride and 1.5 parts of polyethyleneimine.

[0094] The preparation of the polarizing plate includes the following steps:

[0095] Step 1: Add deionized water to the container, keep it warm at 30°C and stir evenly, then add polyvinyl alcohol powder to the beaker in small amounts and multiple times, stir and disperse at high speed for 1 hour, then heat to 95°C, stir for 2 hours, until the polyvinyl alcohol is completely dissolved; then add lithium magnesium powder, continue stirring for 2 hours, during which the mass of deionized water that is volatilized and reduced is supplemented to ensure the solid content of the stock solution, and obtain a semi-finished adhesive.

[0096] Step 2: Add zirconium chloride to the semi-finished adhesive, stir at high speed for 15 minutes, cool the semi-finished adhesive to 25-30° C., add glutaraldehyde and polyethyleneimine to obtain a water-resistant polyvinyl alcohol optical adhesive.

[0097] Step 3: Use roller coating to apply water-resistant polyvinyl alcohol optical adhesive on the upper and lower surfaces of the polyvinyl alcohol film that has been dyed with iodine or dye and stretched, and then use roller lamination to laminate the upper and lower surfaces of the polyvinyl alcohol film with triacetyl cellulose film to form a polarizing plate. After lamination, use segmented drying for a total of 6 stages, and the drying temperatures of each stage are 60, 60, 65, 70, 75, 85, and 85°C.

[0098] Example 12

[0099] A water-resistant polyvinyl alcohol optical adhesive is prepared by mixing the following components in parts by weight: 94.2 parts of deionized water, 3 parts of polyvinyl alcohol powder (average polymerization degree 2500, saponification degree 98%), 1 part of leonite powder, 0.2 parts of glutaraldehyde, 0.25 parts of zirconium sulfate and 1.5 parts of polyethyleneimine.

[0100] The preparation of the polarizing plate includes the following steps:

[0101] Step 1: Add deionized water to the container, keep it warm at 30°C and stir evenly, then add polyvinyl alcohol powder to the beaker in small amounts and multiple times, stir and disperse at high speed for 1 hour, then heat to 95°C, stir for 2 hours, until the polyvinyl alcohol is completely dissolved; then add lithium magnesium powder, continue stirring for 2 hours, during which the mass of deionized water that is volatilized and reduced is supplemented to ensure the solid content of the stock solution, and obtain a semi-finished adhesive.

[0102] Step 2: Add zirconium sulfate to the semi-finished adhesive, stir at high speed for 15 minutes, cool the semi-finished adhesive to 25-30° C., add glutaraldehyde and polyethyleneimine to obtain a water-resistant polyvinyl alcohol optical adhesive.

[0103] Step 3: Use roller coating to apply water-resistant polyvinyl alcohol optical adhesive on the upper and lower surfaces of the polyvinyl alcohol film that has been dyed with iodine or dye and stretched, and then use roller lamination to laminate the upper and lower surfaces of the polyvinyl alcohol film with triacetyl cellulose film to form a polarizing plate. After lamination, use segmented drying for a total of 6 stages, and the drying temperatures of each stage are 60, 60, 65, 70, 75, 85, and 85°C.

[0104] Test example:

[0105] The polarizing plates prepared in Examples 1-12 and Comparative Example 1 were tested in the following manner:

[0106] 1. The viscosity of the adhesive is tested by RVDV1M equipment at a test temperature of 25±0.1℃

[0107] 2. Polarizer boiling resistance test: A 60*40mm polarizer cut at 0° and coated with PSA glue is attached to the glass and placed in a water steamer at 100℃*100%RH for 30min and 60min.

[0108] In order to intuitively understand the test effects of the adhesives of Examples 1-12 and Comparative Example 1, they are now listed in Table 1. Figure 2 The comparative effect diagram of the boiling resistance of the polarizing plate in Comparative Example 1 and Example 1 is shown.

[0109] Table 1 Test results

[0110]

[0111]

[0112] Table 1 and Figure 2 The test results show that the polarizing plate prepared only by the adhesive based on chemical bond cross-linking cannot withstand the extreme high temperature and high humidity conditions of 100℃*100%RH. Thanks to the stacking assembly trend and strong hydrogen bonding of the lithium magnesium powder in the adhesive, supplemented by the binary, ternary and multi-chemical bonds formed by glutaraldehyde, polyethyleneimine and metal salts with the acetoacetyl functional groups in polyvinyl alcohol, the organic / inorganic hybrid polyvinyl alcohol optical adhesive provided in this embodiment can effectively enhance the water resistance of the polarizing plate.

[0113] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A water-resistant polyvinyl alcohol optical adhesive, characterized in that: The composition comprises, by weight: 88-95 parts of deionized water, 4-7 parts of polyvinyl alcohol, 0.1-2 parts of foresite powder, 0.1-2 parts of glutaraldehyde, 0.1-0.5 parts of metal salt and 0.1-2 parts of polyethyleneimine.

2. The water-resistant polyvinyl alcohol optical adhesive according to claim 1, characterized in that: The average polymerization degree of the polyvinyl alcohol is 1000-2500.

3. The water-resistant polyvinyl alcohol optical adhesive according to claim 1, characterized in that: The saponification degree of the polyvinyl alcohol is 90-99%.

4. The water-resistant polyvinyl alcohol optical adhesive according to claim 1, characterized in that: The average polymerization degree of the polyethyleneimine is 1000-2500.

5. The water-resistant polyvinyl alcohol optical adhesive according to claim 1, characterized in that: The length and width of the lithium magnesium stone powder are both between 0.3-1 μm, and the thickness of the powder is between 0.01-0.04 μm.

6. The water-resistant polyvinyl alcohol optical adhesive according to claim 1, characterized in that: The metal salt is one or more of magnesium chloride, magnesium sulfate, aluminum chloride, aluminum sulfate, zirconium chloride and zirconium sulfate.

7. A method for preparing the water-resistant polyvinyl alcohol optical adhesive according to any one of claims 1 to 6, characterized in that: Includes steps: Mix polyvinyl alcohol and deionized water according to weight ratio, heat to 90-95°C, add levofloxacin powder after stirring, and continue stirring to obtain a semi-finished adhesive; Add metal salt to the semi-finished adhesive in parts by weight, then cool the semi-finished adhesive to 25-30° C., add polyethyleneimine and glutaraldehyde in sequence, and continue stirring to obtain the water-resistant polyvinyl alcohol optical adhesive.

8. An application of the water-resistant polyvinyl alcohol optical adhesive according to any one of claims 1 to 6, characterized in that: The water-resistant polyvinyl alcohol optical adhesive is used to prepare a polarizing plate.

9. The use according to claim 8, characterized in that: The preparation of the polarizing plate comprises the following steps: The water-resistant polyvinyl alcohol optical adhesive is applied on the upper and lower surfaces of the polyvinyl alcohol film dyed with iodine or dye and stretched by roller coating; The upper and lower surfaces of the polyvinyl alcohol film are respectively laminated to the triacetyl cellulose film by roller lamination, and after lamination, segmented drying is performed to obtain the polarizing plate.

10. The use according to claim 9, characterized in that: The temperature of the segmented drying is 40-100° C., and the thickness of the water-resistant polyvinyl alcohol optical adhesive after drying is 2-5 μm.

Citation Information

Patent Citations

  • Polarizing film, method for producing same, optical film, and image display device

    US10858553B2

  • Adhesive composition, adhesive layer, optical film provided with adhesive layer, image display panel, and liquid crystal display

    US11008485B2

Cited By

  • Adhesive for polarizing element, polarizing element and preparation method of adhesive

    CN116262872A